An Old Man in Action: the Relations between Generations in 14^th Century Zadar - Nikolić Zrinka (2005)
In this paper I deal with an old man from Zadar and his conduct during the last decades of his life. Of particular interest is his conduct at the court of Zadar in disputes over family inheritance as well as the reactions of his family and court regarding this.